PENENTUAN DESA MISKIN Analisis Potensial Desa 1990 - Tukiran Tukiran (Populasi, 1993)
The 1990 Village Potential Census (PODES) aims at collecting data on village capabilities, land utilities, transportations, population and environment, and agricultural, economics, educational and health activities in order to investigate village development in Indonesia. Part of the existing data is utilized for compiling sume indicators on poor and non-poor villages. To obtain certain criteria on poverty, 27 variables have been selected for the rural-villages regions and 25 variables for urban villages which are assumed as being relevant of being poor. The criteria of poverty is based on the total score average, village total score, and deviation standard.The result of the analysis only show the location of poor villages, and not the existing number of poor population. The criteria about a poor village should be extremely carefully utilized since part of the selected variables is based on the reports of majority of the village population only, so that the benefit becomes very limited. Information about these poor villages is more suited for the parameters of poor village facilities and infrastuctures. Information about poor villages, according to PODES, has several basic weaknesses which can be improved with the support of the data of the 1993 Agricultural Census or the 1994 National Socioeconomyc Survey.